Battery, preparation method thereof and electric equipment

By adding lithium supplementary particles to the positive electrode active layer of the lithium-ion battery, designing localized distribution characteristics in the electrolyte, and using ionic additives to capture oxygen, the problem of electrolyte decomposition in the Li5FeO4 activated lithium release reaction is solved, and the energy efficiency and life of the battery are improved.

CN119833752AActive Publication Date: 2025-04-15XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411799629.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-15
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

How to inhibit the decomposition of electrolyte in activated lithium-release reaction of Li5FeO4 in lithium-ion batteries and improve the energy efficiency of lithium iron phosphate batteries.

Method used

By adding lithium-fuel particles to the positive electrode active layer of the battery and designing localized distribution characteristics in the electrolyte, the oxygen released by the lithium-fuel particles is captured using ionic additives to reduce the decomposition of the electrolyte.

Benefits of technology

It effectively improves the battery's circulation capacity retention rate and energy efficiency, and extends the battery's circulation service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833752A_ABST
    Figure CN119833752A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and particularly discloses a battery, a preparation method thereof and electric equipment. The battery comprises a positive pole piece, a negative pole piece, a diaphragm and an electrolyte, wherein the positive pole piece comprises a positive active layer and a current collector, the positive active layer is arranged on the surface of the current collector, and the positive active layer comprises lithium supplementing particles; the diaphragm is arranged between the positive pole piece and the negative pole piece; the electrolyte comprises a non-free electrolyte and a free electrolyte, and the non-free electrolyte comprises an electrolyte in the pores of the positive pole piece, an electrolyte in the pores of the negative pole piece and an electrolyte in the pores of the diaphragm; the non-free electrolyte comprises an ionic additive, and the mass ratio m of the ionic additive in the non-free electrolyte is more than or equal to 0.001% and less than or equal to 2%; and the R value Re of the free electrolyte under the lithium potential is more than 0 and less than 1. Therefore, the battery provided by the invention has excellent energy efficiency and relatively long cycle service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery and a preparation method thereof, and electrical equipment. Background Art

[0002] Lithium-ion batteries with lithium iron phosphate (LiFePO4) positive electrode and graphite negative electrode system have the characteristics of low cost and excellent safety, and are suitable for the field of electrochemical energy storage. The formation of SEI film (negative electrode / electrolyte interface film) on the anode side consumes the active lithium of the cathode during the first charging process, resulting in a decrease in battery capacity and low charging and discharging efficiency. In order to further optimize the efficient use of resources, promote sustainable development, and improve the energy efficiency of lithium iron phosphate batteries, the first irreversible capacity loss of lithium batteries can be effectively compensated by adding lithium supplement materials to the positive electrode materials.

[0003] One of the most practical pre-lithiation agents is Li5FeO4 (LFO), which has broad application prospects due to its high theoretical specific capacity (867mAh / g) and low cost. In addition, LFO is suitable for the current lithium-ion battery system. By mixing an appropriate amount of LFO with conventional positive electrode materials, the initial charging capacity of the relevant positive electrode materials can be increased, thereby achieving the lithium supplement effect. However, the pre-lithiation agent LFO will simultaneously undergo iron and oxygen oxidation reactions during the delithiation process, resulting in the decomposition of the electrolyte and the accumulation of by-products at the pole piece, which reduces the battery life and energy efficiency.

[0004] Therefore, how to inhibit the decomposition of electrolyte during the LFO activation and lithium release reaction is a technical challenge to improve the energy efficiency of lithium iron phosphate batteries. Summary of the invention

[0005] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0006] In the first aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the positive electrode sheet includes a positive electrode active layer and a current collector, the positive electrode active layer is arranged on the surface of the current collector, and the positive electrode active layer includes lithium supplement particles; the separator is arranged between the positive electrode sheet and the negative electrode sheet; the electrolyte includes a non-free electrolyte and a free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the separator; the non-free electrolyte includes an ionic additive, and the mass proportion m of the ionic additive in the non-free electrolyte is: 0.001%≤m≤2%; the R value R of the free electrolyte at the lithium potential is e =0<R e <1.

[0007] The applicant can improve the cycle capacity retention rate and energy efficiency of the battery by designing the localized distribution characteristics of the free electrolyte and the non-free electrolyte. Among them, the non-free electrolyte contains ionic additives. After charging, the reduction products of the anions in the ionic additives can react with the oxygen free radicals / oxygen released by the lithium supplement particles to reduce the oxygen content in the system. When the mass proportion of the ionic additives in the non-free electrolyte is controlled to be 0.001%-2%, the ionic additives can be enriched in the pores of the electrode, and their reduction products are fully combined with the lithium supplement particles during the formation process, and there will be no insufficient oxygen capture capacity due to insufficient addition, or excessive addition will cause CEI (positive electrode / electrolyte interface film) impedance and cycle deterioration; when the R value of the free electrolyte at the lithium potential is controlled to be a value in the range of 0-1 (not 0 or 1), the accumulation of by-products on the surface of the electrode can be avoided. Therefore, by simultaneously controlling the mass proportion of ionic additives in the non-free electrolyte and the R value of the free electrolyte at the lithium potential, the overflow of gases such as methane, ethylene, and carbon dioxide, as well as the production of by-products such as lithium alkylate and lithium carbonate can be reduced, thereby effectively improving the energy efficiency of the battery and extending the cycle life of the battery.

[0008] According to an embodiment of the present application, the battery may further include at least one of the following additional technical features:

[0009] According to the embodiment of the present application, the battery satisfies the following conditions: 0<m / R e ≤2.5%, wherein m is the mass proportion of the ionic additive in the non-free electrolyte, R e is the R value of the free electrolyte at the potential relative to lithium.

[0010] According to an embodiment of the present application, the mass proportion of the lithium supplement particles in the positive electrode active layer is 0.3%-3%.

[0011] According to an embodiment of the present application, the lithium supplement particle includes a matrix and a coating layer, and the coating layer is arranged on the periphery of the matrix.

[0012] According to an embodiment of the present application, the ionic additive includes at least one of bis(oxalatoborate), difluoro(oxalatoborate), tri(oxalatophosphate), difluorobis(oxalatophosphate), and tetrafluoro(oxalatophosphate).

[0013] According to an embodiment of the present application, the matrix is ​​Li5FeO4.

[0014] According to an embodiment of the present application, the coating layer comprises oxide and carbon, wherein the chemical formula of the oxide is Z x O y, Z is selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, 1≤x≤3, 1≤y≤5.

[0015] According to an embodiment of the present application, the coating layer has a thickness of 0.001 μm-1 μm.

[0016] In the second aspect of the present application, the present application proposes a method for preparing the battery described in the first aspect. According to an embodiment of the present application, the method comprises the following steps of injecting electrolyte: performing a first injection treatment using a first electrolyte; performing a formation treatment after the first injection treatment; and performing a second injection treatment using a second electrolyte after the formation treatment, wherein the first electrolyte comprises an ionic additive.

[0017] Therefore, the present application adopts a secondary injection method to prepare the electrolyte, that is, by separating the electrolyte components required for the battery formation stage and the electrolyte components required for the circulation stage, the local distribution characteristics of the non-free electrolyte and the free electrolyte can be achieved. Among them, the first electrolyte is used to generate the initial SEI and CEI. The part of the first electrolyte remaining in the pores of the pole piece and the diaphragm after the formation reaction, that is, the non-free electrolyte in the initial state, is closest to the active material. Therefore, the ionic additive in the first electrolyte is conducive to the negative polarization to form the initial SEI, and the remaining ionic additive is enriched in the pores of the positive pole piece, which can capture the oxygen released by the lithium supplement particles in time. The second electrolyte is used to supplement the electrolyte required for long circulation. When the first electrolyte is excessive, the part that is not consumed or enters the pores of the diaphragm and the pole piece merges with the second electrolyte to form a free electrolyte in the initial state.

[0018] According to an embodiment of the present application, the method may further include at least one of the following additional technical features:

[0019] According to an embodiment of the present application, the method satisfies the following conditions: 0.7≤(1-m) / M≤0.95, wherein m is the mass proportion of the ionic additive in the non-free electrolyte, and M is the mass proportion of the ionic additive in the first electrolyte.

[0020] According to an embodiment of the present application, the R value R of the second electrolyte at the lithium potential is z 0.1≤R z ≤3.

[0021] According to an embodiment of the present application, the maximum charging voltage of the formation treatment is 3.9V-4.6V.

[0022] According to an embodiment of the present application, the mass ratio of the first electrolyte to the second electrolyte is (6:4)-(9:1).

[0023] According to an embodiment of the present application, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5g / Ah-5g / Ah.

[0024] In the third aspect of the present application, the present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes the battery described in the first aspect, or a battery prepared by the method described in the second aspect. As mentioned above, the battery of the present application has excellent energy efficiency and cycle capacity retention rate, so the electrical device of the present application also has good energy density and cycle life. Those skilled in the art will understand that this application has all the features and advantages of the battery described above, and will not be repeated here.

[0025] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0027] Figure 1 A flow chart of a method for preparing an electrolyte in a battery according to an embodiment of the present application is shown. DETAILED DESCRIPTION

[0028] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0029] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0030] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0031] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0032] In the description of the present application, “plurality” means two or more.

[0033] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0034] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0035] By adding lithium-replenishing particles to the positive electrode active layer, the positive electrode lithium-rich electrode sheet releases lithium ions using the lithium-replenishing particles as a "sacrificial agent" during the first cycle of charging to replenish the irreversible lithium consumed by the formation of the SEI film at the negative electrode, thereby increasing the energy density of the battery. However, when lithium-replenishing particles release lithium ions, they also release oxygen. Under high voltage, oxygen will accelerate the decomposition reaction of components in the electrolyte, especially during high-temperature formation or high-temperature static aging, the reduction and oxidation decomposition of the electrolyte are more serious. This causes a large amount of methane, ethylene, carbon dioxide and other gases to overflow, and a large amount of lithium alkylates and lithium carbonate to accumulate on the surface of the electrode, which in turn causes a decrease in energy efficiency and shortens the cycle life.

[0036] Generally, the methods to inhibit the decomposition of electrolyte in the LFO activation and lithium release reaction include: modification of lithium supplement materials by doping, morphology control, surface coating, etc.; using phosphate compounds, nitrogen-containing compounds, sulfonate compounds, etc. as electrolyte additives to inhibit oxidation reaction and gas production. However, the above measures will cause the positive electrode protective layer to be significantly thickened, the impedance to increase, the ion conductivity to decrease, and the battery energy efficiency to deteriorate.

[0037] Therefore, the applicant has developed a new battery, which has a localized and differentially designed electrolyte according to the potential of the lithium-replenishing particle-specific delithiation reaction platform, so that the battery cell has a non-free electrolyte and a free electrolyte. Among them, the non-free electrolyte contains an ionic additive, and the anion of the ionic additive can be enriched in the pores under the action of the electric field during the charging process, and the oxygen released by the lithium-replenishing particles is captured in time, and its diffusion into the free electrolyte is inhibited to accelerate the electrolyte decomposition reaction, thereby improving the energy efficiency and cycle capacity retention rate of the battery. The battery and its preparation method will be described in detail below.

[0038] Battery

[0039] In the first aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the positive electrode sheet includes a positive electrode active layer and a current collector, the positive electrode active layer is arranged on the surface of the current collector, and the positive electrode active layer includes lithium supplement particles; the separator is arranged between the positive electrode sheet and the negative electrode sheet; the electrolyte includes a non-free electrolyte and a free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the separator; the non-free electrolyte includes an ionic additive, and the mass proportion m of the ionic additive in the non-free electrolyte is: 0.001%≤m≤2%; the R value R of the free electrolyte at the lithium potential e =0<R e <1.

[0040] The applicant has improved the cycle capacity retention rate and energy efficiency of the battery by designing the localized distribution characteristics of the free electrolyte and the non-free electrolyte. Among them, the non-free electrolyte contains an ionic additive, the oxidation reactant of which is rich in organic components and has a nonlinear three-dimensional structure. This component is attached to the lithium supplement particles, and the CEI formed has high conductivity, which blocks the further oxidation and decomposition of the solvent molecules. The applicant found in the experiment that the amount of ionic additive added and the R value (R e ) play an important role in the performance of the battery. When the amount of ionic additive added at the first time is controlled, the ionic additive can be enriched in the pores of the electrode, and its reduction product is fully combined with the lithium supplement particles during the formation process, and insufficient oxygen capture capacity due to insufficient addition or excessive CEI impedance due to excessive addition will not occur. When the R value (R e ), the oxidation window of the free electrolyte is increased, and a large amount of by-products are avoided. Therefore, by simultaneously controlling the mass proportion of the ionic additive in the non-free electrolyte and the R value of the free electrolyte at the lithium potential, the overflow of gases such as methane, ethylene, and carbon dioxide, as well as the generation of by-products such as lithium alkylate and lithium carbonate can be reduced, thereby effectively improving the energy efficiency of the battery and extending the cycle life of the battery.

[0041] Specifically, when the mass proportion m of the ionic additive in the non-free electrolyte is 0.001%≤m≤2%, the ionic additive can be enriched in the pores of the electrode, and its reduction product can be fully combined with the lithium supplement particles during the formation process, and insufficient oxygen capture capacity due to insufficient addition, or excessive CEI impedance and cycle deterioration due to excessive addition will not occur. Specifically, the mass proportion of the ionic additive in the non-free electrolyte can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc., or can be a range composed of any of the above values.

[0042] Specifically, when the R value R of the free electrolyte at the lithium potential is e 0<R e When R is less than 1, the by-products can be prevented from accumulating on the electrode surface. e The value represents the electrochemical stability of the ionic medium in the battery cell, R e is the R value of the free electrolyte at the lithium potential. In addition, the voltage value set for the formation process is U max +0.1V, where U max It needs to be no less than the highest delithiation reaction platform potential of the lithium supplement particles, so that the lithium supplement particles in the positive electrode active layer can be effectively activated and delithiated during the battery manufacturing process to provide the required energy. The value of the lithium potential is U max , for R under lithium potential e The upper limit indicates that the free electrolyte will not decompose seriously when the lithium replenishment reaction occurs. e The closer to 0, the better the electrochemical stability of the free electrolyte at this voltage. Specifically, the R value R of the free electrolyte at the lithium potential is e It may be 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.99, etc., or may be a range consisting of any of the above values.

[0043] It should be noted that U max Greater than or equal to the highest delithiation reaction platform potential of the lithium supplement particle. If the lithium supplement particle has two or more delithiation reaction platform potentials, the highest delithiation reaction platform potential shall prevail.

[0044] In some embodiments of the present application, the battery satisfies the following conditions: 0<m / R e ≤2.5%; wherein m is the mass proportion of the ionic additive in the non-free electrolyte, R e is the R value of the free electrolyte at the potential to lithium. For example, m / R eIt can be 0.1%, 0.2%, 0.5%, 0.7%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, etc., or can be any range of the above values. The applicant has found that when the non-free electrolyte does not contain ionic additives, that is, m / R e When m / R is 0, it is impossible to capture the oxygen released by the lithium supplement particles and inhibit its diffusion into the free electrolyte to accelerate the decomposition reaction of the electrolyte; when the amount of ionic additive added is too high or the free electrolyte is too large, that is, m / R e If the ratio is higher than 2.5%, lithium ion insertion and extraction will be affected, resulting in increased impedance and deterioration of energy efficiency. e Meeting the above range can effectively capture the oxygen released by the lithium supplement particles and inhibit the decomposition of the electrolyte while ensuring the normal deintercalation of lithium ions.

[0045] In some embodiments of the present application, the non-free electrolyte includes electrolyte in the pores of the positive electrode plate, electrolyte in the pores of the negative electrode plate and electrolyte in the pores of the diaphragm, and the rest is free electrolyte. Among them, the non-free electrolyte is in direct contact with the electrode and the diaphragm, dominates the formation and repair process of SEI, participates in the desolvation effect of lithium ions, and directly determines the SEI membrane impedance R in the battery. SEI and the charge transfer resistance R ct ; The free electrolyte exists in the battery cell cavity outside the material pores, and there is no absolute physical barrier with the non-free electrolyte. When the non-free electrolyte is insufficiently consumed, the free electrolyte is automatically absorbed as a supplement through the capillary action of the pole piece and the diaphragm. When the content of a certain component in the non-free electrolyte is higher than that of the free electrolyte, the content of the component decreases after the non-free electrolyte absorbs the free electrolyte; when the content of a certain component in the non-free electrolyte is lower than that of the free electrolyte, the content of the component increases after the non-free electrolyte absorbs the free electrolyte. There are dynamic differences in the electrolyte composition of the two regions during the cycle consumption process, so the component content of the battery during use also changes dynamically.

[0046] In some embodiments of the present application, the ionic additive includes but is not limited to at least one of bis(oxalato)borate, difluoro(oxalato)borate, tri(oxalato)phosphate, difluorobis(oxalato)phosphate, and tetrafluoro(oxalato)phosphate. Thus, after charging, the reduction products generated by the anions of the above-mentioned types of ionic additives can react with oxygen free radicals / oxygen, and the intermediate reaction products of the anions and the remaining anions that have not been consumed will tend to be enriched at the positive electrode due to the electric field, further playing a role in quickly capturing oxygen.

[0047] It should be noted that, as long as the technical effect of the present invention is not impaired, there is no particular limitation on the type of cations combined with anions in the ionic additives described in the present application. As a specific embodiment of the present application, the cations may include metal cations such as lithium, sodium, potassium, magnesium, calcium, and onium cations such as tetraalkylammonium, tetraalkylphosphonium, and imidazolium derivatives, preferably lithium ions.

[0048] In some embodiments of the present application, the mass proportion of lithium-supplementing particles in the positive electrode active layer is 0.3%-3%. For example, it can be 0.3%, 0.5%, 0.7%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, 2.7%, 3%, etc., or it can be a range composed of any of the above values. Therefore, by making the mass proportion of lithium-supplementing particles within the above range, on the one hand, it can release enough lithium ions as a "sacrificial agent" to supplement the irreversible lithium consumed by the formation of SEI film in the negative electrode, thereby improving the energy density of the battery; on the other hand, it can reduce the released oxygen content and avoid the generation of excessive gas and by-products, thereby avoiding the reduction of energy efficiency and shortening the cycle life.

[0049] In some embodiments of the present application, the lithium supplement particles include a matrix and a coating layer, wherein the coating layer is arranged on the periphery of the matrix. The matrix can release lithium ions, thereby increasing the energy density of the battery. The coating layer can prevent the matrix from reacting with air and being oxidized, which is beneficial to improving the stability of the matrix. On the other hand, the coating layer has conductive properties, reduces the lithium ion deintercalation impedance and polarization reaction, and is beneficial to improving the energy efficiency of the battery.

[0050] In some embodiments of the present application, the matrix is ​​Li5FeO4. Therefore, the Li5FeO4 can release more lithium ions and improve the energy density of the battery.

[0051] In some embodiments of the present application, the coating layer includes oxide and carbon, wherein the chemical formula of the oxide is Z x O y , Z is selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, 1≤x≤3, 1≤y≤5. Among them, the oxide can prevent the core from being oxidized and corroded by the outside world; carbon is used to improve the conductivity of the coating layer. It should be noted that the oxide in the coating layer can be one or more, and the chemical formula of the multiple oxides is Z x O y .

[0052] In some embodiments of the present application, the mass of the oxide accounts for 0.1wt% to 20wt% of the coating layer, for example, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., or a range of any of the above values.

[0053] In some embodiments of the present application, the thickness of the coating layer is 0.001 μm-1 μm. For example, it can be 0.001 μm, 0.005 μm, 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, etc., or it can be a range composed of any of the above values. Thus, by making the thickness of the coating layer within the above range, it is possible to improve the stability of the substrate while ensuring the normal release of lithium ions from the substrate, and avoid oxidation and corrosion by the outside world. If the thickness of the coating layer is too thick, the deintercalation potential of the active material will be too high. If the thickness of the coating layer is too thin, the coating integrity cannot be guaranteed.

[0054] In some embodiments of the present application, the positive electrode active layer further includes a positive electrode active material.

[0055] Exemplarily, when the positive electrode plate is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, or a composite material of lithium iron manganese phosphate and carbon.

[0056] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0057] In some embodiments of the present application, the positive electrode active layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0058] In some embodiments of the present application, the positive electrode active layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0059] In some embodiments of the present application, the negative electrode plate includes a negative electrode active layer and a negative electrode current collector, and the negative electrode active layer includes a negative electrode active material.

[0060] In some embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon carbon composites, silicon nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0061] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite negative electrode current collector. For example, as the metal foil, a copper foil may be used. The composite negative electrode current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite negative electrode current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0062] In some embodiments of the present application, the negative electrode active layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0063] In some embodiments of the present application, the negative electrode active layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0064] In some embodiments of the present application, the negative electrode active layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0065] The present invention has no particular limitation on the type of the separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. According to an embodiment of the present application, the separator can be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0066] In some embodiments of the present application, the battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.

[0067] In some embodiments of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0068] In some embodiments of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0069] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0070] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0071] Method for preparing battery

[0072] In a second aspect of the present application, the present application proposes a method for preparing the battery described in the first aspect. According to an embodiment of the present application, referring to Figure 1 , the method comprising:

[0073] S100: First injection process

[0074] In this step, the first electrolyte is injected for the first time, and the first electrolyte includes an ionic additive. The first electrolyte is used to generate the initial SEI and CEI. The first electrolyte is the part that remains in the pores of the pole piece and the diaphragm after the reaction, which is the non-free electrolyte in the initial state, and is closest to the active material. Therefore, adding the ionic additive to the first electrolyte is conducive to the negative polarization to form the initial SEI, and the remaining ionic additive is enriched in the pores of the positive pole piece, which can capture the oxygen released by the lithium supplement particles in time.

[0075] In some embodiments of the present application, the method satisfies the following conditions: 0.7≤(1-m) / M≤0.95, wherein m is the mass proportion of the ionic additive in the non-free electrolyte, and M is the mass proportion of the ionic additive in the first electrolyte. The applicant has established a relationship between the manufacturing process parameters (the mass proportion of the ionic additive in the first electrolyte) and the battery characteristic parameters (the mass proportion of the ionic additive in the non-free electrolyte). This formula can ensure that the mass percentage of the ionic additive consumed during the manufacturing process is 50% or more and is not completely consumed, thereby indicating that the ionic additive participates in the negative polarization to form the initial SEI, and there is still residual ionic additive that can be used to capture the oxygen released by the lithium supplement particles.

[0076] S200: Chemical treatment

[0077] In this step, the battery cell after the first liquid injection treatment is subjected to a formation treatment, so that part of the electrolyte remaining in the gaps between the pole piece and the diaphragm after the formation treatment forms a non-free electrolyte in the initial state.

[0078] In some embodiments of the present application, the maximum charging voltage value of the formation treatment is (U max +0.1V), the (U max +0.1V) is 3.9V-4.6V. As some specific examples, (U max +0.1V) can be 3.9V, 4.0V, 4.1V, 4.2V, 4.3V, 4.4V, 4.5V, 4.6V, etc., or can be a range consisting of any of the above values. max The value is not lower than the highest lithium delithiation reaction platform potential of the lithium supplement particles. Therefore, in the actual manufacture of full batteries with LiFePO4 and graphite negative electrodes, the maximum charging voltage is set to U max +0.1V. Thus, by making the maximum charging voltage (U max +0.1V) within the above range, the lithium supplement particles can be fully activated to achieve the lithium supplement effect, and the over-release of the positive electrode LiFePO4 can be avoided, which would cause irreversible damage to the active material.

[0079] S300: Second injection process

[0080] In this step, the second electrolyte is used to inject the second electrolyte into the battery cell after the formation treatment. The second electrolyte is used to supplement the electrolyte required for the long cycle. When the first electrolyte is excessive, the part that is not consumed by formation or enters the pores of the diaphragm and the electrode will merge with the second electrolyte to form the free electrolyte in the initial state.

[0081] In some embodiments of the present application, the second electrolyte has an R value R at a potential to lithium. z 0.1≤R z ≤3. As some specific examples, R z It can be 0.1, 0.2, 0.5, 0.7, 1, 1.2, 1.5, 1.7, 2, 2.2, 2.5, 2.7, 3, etc., or can be a range consisting of any of the above values. Thus, by making the R value of the second electrolyte at the potential to lithium within the above range, the R value of the free electrolyte can be made e The value satisfies 0<R e <1, so that the free electrolyte has a higher electrochemical stability, ensuring the role of fast ion channel. z Compared with the free electrolyte R e The slightly higher value is because the second electrolyte may contain additives that may oxidize the solvent in advance, which will generate a reaction current. The reaction current will cause R zThe value is relatively large, but this part of the additive will be slightly consumed during the injection process and capacity test, which will reduce this part of the additive, thereby making the R e The value decreases.

[0082] In some embodiments of the present application, the mass ratio of the first electrolyte to the second electrolyte is (6:4)-(9:1). As some specific examples, the mass ratio of the first electrolyte to the second electrolyte can be 6:4, 7:3, 8:2, 9:1, etc., or can be a range composed of any of the above numerical values. During the experiment, the applicant divided the total electrolyte demand of the battery into the first injection demand and the second injection demand in proportion, and obtained the above-mentioned proportion range that can achieve the effect of the present application through testing. When this range is exceeded, it will no longer have the effect of improving overcharge thermal runaway. This may be due to the fact that the ratio of the injection volume of the first injection treatment to the injection volume of the second injection treatment is too low, that is, less than 6:4, then the injection volume of the first injection (the first injection treatment) is insufficient for sufficient infiltration, the SEI protective layer obtained by the chemical formation treatment is uneven and has poor thermal stability, and after the second injection (the second injection treatment), there is no SEI area formed and the electrolyte is electronically conductive, resulting in the accumulation of electrolyte decomposition by-products; the ratio of the injection volume of the first injection treatment to the injection volume of the second injection treatment is too high, that is, greater than 9:1, then the proportion of the second injection is low, the free electrolyte components mainly come from the electrolyte components that have not been consumed in the first injection treatment, and are basically the same as the non-free electrolyte components. At this ratio, there is basically no difference between the secondary injection and the traditional primary injection, and it is difficult to achieve the design of localized electrolyte.

[0083] It should be noted that, since the absolute mass of the second electrolyte during the second injection treatment will be adjusted according to the capacity of different batteries, the present application is applicable to battery systems of various capacities, so the present application does not limit the specific injection amount of the electrolyte.

[0084] In some embodiments of the present application, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5g / Ah-5g / Ah. As some specific examples, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 2.5g / Ah, 2.7g / Ah, 3g / Ah, 3.2g / Ah, 3.5g / Ah, 3.7g / Ah, 4g / Ah, 4.2g / Ah, 4.5g / Ah, 4.7g / Ah, 5g / Ah, etc., or can be a range composed of any of the above numerical values. According to an embodiment of the present application, the sum of the injection coefficients of the first electrolyte and the second electrolyte is 3.5g / Ah-5g / Ah. Specifically, the injection coefficient (injection amount / cell capacity) represents the electrolyte demand. For lithium-ion batteries for energy storage, a higher injection coefficient can maintain a long cycle life. Therefore, by making the total injection coefficient within the above range, sufficient wetting of the diaphragm and the electrode can be achieved, and local lithium precipitation caused by excessive electrolyte swelling or accumulation at the bottom of the battery can be avoided.

[0085] In some embodiments of the present application, the method for preparing a battery can be carried out through the following steps: a first liquid injection treatment, a static treatment, a formation treatment, a second liquid injection treatment, a high-temperature aging treatment, and a capacity separation treatment to obtain the battery. Among them, the static treatment and the high-temperature aging treatment are not particularly limited, as long as sufficient infiltration and uniform formation and film formation can be guaranteed. The battery can be fully charged and disassembled before the second liquid injection treatment and the capacity separation treatment. Visible electrolyte is distributed at all positions of the positive and negative electrodes and the diaphragm in the battery, and there are no abnormal spots or dark marks on the negative electrode, which meets the requirements. Among them, the full charging process can be charged to 3.65V at a constant current of 0.2C.

[0086] In some embodiments of the present application, the first electrolyte further includes: a first solvent, a first lithium salt and a first additive.

[0087] In some embodiments of the present application, the second electrolyte includes: a second solvent, a second lithium salt, and a second additive.

[0088] In some embodiments of the present application, the first solvent and the second solvent are independently selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, vinylene carbonate (VC), methyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, ethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, propyl vinylene carbonate, 1,2-dipropyl vinylene carbonate, vinyl ethylene carbonate (VEC), divinyl ethylene carbonate (DVEC), methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. Wherein, a part of the hydrogen atoms in the above compounds can be replaced by fluorine atoms.

[0089] In some embodiments of the present application, the first lithium salt and the second lithium salt are independently selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, bis(trifluoromethylsulfonyl)methyl lithium, and tris(trifluoromethylsulfonyl)methyl lithium. According to an embodiment of the present application, the first lithium salt and the second lithium salt are independently selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethylsulfonyl)imide.

[0090] In some embodiments of the present application, the first additive and the second additive are independently selected from at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), 1,4-butane sultone (BS), vinyl sulfate (DTD), tris(trimethylsilane) phosphate (TMSP), adiponitrile (AND), succinonitrile (SN), etc. As long as the type and content of the additives used do not affect the realization of the effect of the present application and can achieve the expected technical effect, they are deemed to be within the scope of technical protection.

[0091] The present application adopts a secondary injection method to prepare the electrolyte, that is, by separating the electrolyte components required for the battery formation stage and the electrolyte components required for the circulation stage, the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery can be achieved. The applicant has found through research that the local distribution characteristics of the electrolyte in the initial state determine the local distribution characteristics of the electrolyte in the subsequent working state: under the premise that the total amount of electrolyte is sufficient and the transmission is unobstructed, the proportion of the local distribution of the solvent in the electrolyte in the initial state can be qualitatively determined by the proportion of the local distribution of the solvent in the electrolyte in the subsequent working state. Therefore, the applicant uses two electrolytes for injection respectively, wherein the first electrolyte is used to generate the initial SEI and CEI, and the part of the first electrolyte remaining in the pores of the pole piece and the diaphragm after the formation reaction, that is, the non-free electrolyte in the initial state, is closest to the active material, so the ionic additive in the first electrolyte is conducive to the negative polarization to form the initial SEI, and the remaining ionic additive is enriched in the pores of the positive pole piece, which can capture the oxygen released by the lithium supplement particles in time. The second electrolyte is used to supplement the electrolyte required for long cycles. When the first electrolyte is in excess, the part that is not consumed or enters the pores of the diaphragm and the electrode will merge with the second electrolyte to form the free electrolyte in the initial state.

[0092] Electrical equipment

[0093] The third aspect of the present invention provides an electrical device. According to an embodiment of the present application, the electrical device includes the battery described in the first aspect or a battery prepared by the method described in the second aspect. Therefore, the electrical device of the present application has high-efficiency energy output and excellent service life and safety performance.

[0094] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0095] As an electrical device, a battery cell, battery module or battery pack can be selected according to its usage requirements.

[0096] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0097] As another embodiment, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery cell may be used as a power source.

[0098] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0099] Example 1

[0100] 1. Preparation of positive electrode sheet:

[0101] The positive electrode active material lithium iron phosphate (LiFePO4), lithium supplement particles (also called lithium supplement, purchased, wherein the matrix is ​​Li5FeO4, the coating layer contains Fe2O3, FeO and carbon, and the total mass of Fe2O3 and FeO in the coating layer accounts for 12%), conductive carbon black (SP), polyvinylidene fluoride (PVDF) in a mass ratio of (97-w):w:2.5:0.5 (w=2), are dispersed in a solvent N-methylpyrrolidone (NMP) and mixed evenly to obtain a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the coating weight per unit area of ​​the positive electrode slurry is 33 mg / cm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained.

[0102] 2. Preparation of negative electrode sheet:

[0103] The negative electrode active material artificial graphite, conductive carbon black (SP), thickener (CMC) and binder (SBR) were dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. The coating weight per unit area of ​​the negative electrode slurry was 16 mg / cm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained.

[0104] 3. Preparation of electrolyte:

[0105] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.1 ppm, the solvent and lithium salt are mixed in a certain proportion, and an ionic additive (lithium difluorooxalatoborate) and other additives are added and stirred until completely dissolved.

[0106] One injection of electrolyte:

[0107] Lithium salt: 8% lithium hexafluorophosphate and 4% lithium bis(fluorosulfonyl)imide by weight;

[0108] Other additives: 3% by weight of vinylene carbonate, 1% by weight of fluoroethylene carbonate, and 1% by weight of vinyl sulfate;

[0109] Ionic additive A: 0.5% by weight of lithium difluorooxalate borate;

[0110] Solvent: EC:EMC:DMC are first mixed in a mass ratio of 1:1:1 and supplemented as the remaining components;

[0111] Second injection of electrolyte:

[0112] Lithium salt: 8% lithium hexafluorophosphate and 4% lithium bis(fluorosulfonyl)imide by weight;

[0113] Other additives: 3% by weight of vinylene carbonate, 1% by weight of fluoroethylene carbonate, and 1% by weight of vinyl sulfate;

[0114] Solvent: EC:EMC:DMC were first mixed in a mass ratio of 1:1:1 and then added as the remaining components.

[0115] 4. Preparation of isolation film: Use 16 μm polyethylene film.

[0116] 5.Battery assembly:

[0117] The prepared positive electrode sheet, separator and negative electrode sheet are stacked in order so that the separator is in the middle of the positive and negative electrodes to separate the positive and negative electrode sheets, and then wound into a bare battery cell. After welding the pole ears, the battery cell is assembled to the outer package, and vacuum dried after hot pressing. Then, a secondary liquid injection process is carried out: the first time the electrolyte is injected, the battery cell is packaged, allowed to stand, and formed, the second time the electrolyte is injected, the battery cell is allowed to stand at high temperature, the capacity is tested, etc., and finally a soft-pack lithium-ion battery with a capacity of 3.2Ah is prepared.

[0118] The formation step is carried out at a pressure of 0.3 MPa and 45°C according to the following prescribed process:

[0119] Step 1: charge to 3V at a constant rate of 0.1C;

[0120] Step 2: Charge to 3.5V at a constant rate of 0.2C, charge to 0.05C at a constant voltage, and let stand for 5 minutes;

[0121] Step 3: Charge at a constant rate of 0.05C to (Umax+0.1V).

[0122] The fixed injection coefficient is 4.0g / Ah; the injection ratio of the first injection and the second injection is 7:3; the static condition after the first injection is 45±5℃ for 24 hours, the formation temperature is 45℃, and the static condition (high temperature aging) after the second injection is 45±5℃ for 24 hours. Umax=3.9V, that is, the maximum voltage of the above battery formation step is 4.0V.

[0123] Example 2-18

[0124] 1. The positive electrode sheet was prepared according to the method described in Example 1, and the value of w is shown in Table 1;

[0125] 2. Preparation of electrolyte:

[0126] The difference between Examples 2-8 and 13-17 and Example 1 is that the type and amount of the ionic additive A in one injection of the electrolyte are different, as shown in Table 1; the components of the two injections of the electrolyte are the same.

[0127] In Examples 9-12, the composition of the first electrolyte is the same as that of Example 2, and the composition of the lithium salt in the second electrolyte is different from that of Example 2, wherein:

[0128] Example 9: 6% by weight of lithium hexafluorophosphate and 4% by weight of lithium bis(fluorosulfonyl)imide;

[0129] Example 10: 10% by weight of lithium hexafluorophosphate and 2% by weight of lithium bis(fluorosulfonyl)imide;

[0130] Example 11: 12% by mass of lithium hexafluorophosphate;

[0131] Example 12: The weight percentage of lithium hexafluorophosphate is 11% and the weight percentage of lithium bis(fluorosulfonyl)imide is 3%.

[0132] In Example 18, the type and amount of ionic additive A in one injection of electrolyte are as listed in Table 1; the lithium salt in the second injection of electrolyte is 10% lithium hexafluorophosphate and 2% lithium bis(fluorosulfonyl)imide by weight, and the solvents EC:EMC:DMC are first mixed in a weight ratio of 1:1:1 and supplemented as the remaining components.

[0133] Comparative Examples 1-9

[0134] Comparative Example 1 is a one-time liquid injection process, and the electrolyte components and proportions are consistent with the one-time electrolyte injection of Example 2.

[0135] Comparative Examples 2-3 are secondary liquid injection processes, wherein the first electrolyte of Comparative Examples 2 and 3 is 8% lithium hexafluorophosphate and 4% lithium bisfluorosulfonyl imide in terms of lithium salt mass ratio, and the other additives are 3% vinyl carbonate, 1% fluoroethylene carbonate, and 1% vinyl sulfate in terms of mass ratio, and the solvents EC:EMC:DMC are first mixed at a mass ratio of 1:1:1 and supplemented as the remaining components; in the second electrolyte of Comparative Example 2, the lithium salt mass ratio is 8% lithium hexafluorophosphate and 4% lithium bisfluorosulfonyl imide, and the other additives are 3% vinyl carbonate, 1% fluoroethylene carbonate, and 1% vinyl sulfate in terms of mass ratio, and the solvents EC:EMC:DMC are first mixed at a mass ratio of 1:1:1 and supplemented as the remaining components; the components and proportions of the second electrolyte of Comparative Example 3 are consistent with those of the first electrolyte of Example 2;

[0136] Comparative Example 4 is a secondary injection process, and the first and second electrolyte injections of Comparative Example 4 are consistent with those of Example 2, except that Comparative Example 4 does not contain a lithium supplement;

[0137] Comparative Examples 5-7 are two-time injection processes, wherein the components of the second injection electrolyte of Comparative Examples 5-7 are the same as those of Example 1, and the first injection electrolyte is different from that of Example 1, and the specific difference is that the content of the ionic additive A is different. The specific content of the ionic additive A in Comparative Examples 5-7 is shown in Table 1;

[0138] Comparative Example 8 is a two-time liquid injection process. The composition of the first injection of the electrolyte in Comparative Example 8 is the same as that in Example 2, and the composition of the lithium salt in the second injection of the electrode solution is different from that in Example 2, specifically: 6% by weight of lithium hexafluorophosphate and 2% by weight of lithium bis(fluorosulfonyl)imide;

[0139] Comparative Example 9 is a secondary injection process. The components of the first injection electrolyte and the second injection electrolyte of Comparative Example 9 are the same as those of Example 1. The specific difference is the content of the lithium supplement agent. The content of the lithium supplement agent of Comparative Example 9 is shown in Table 1.

[0140] The specific parameters in Examples 1-18 and Comparative Examples 1-9 are shown in Table 1.

[0141] Table 1

[0142]

[0143]

[0144] Performance Test:

[0145] 1. Test of positive electrode lithium supplement particles:

[0146] Through a scanning electron microscope (SEM), it is easy to see the matrix, coating and components of the lithium-supplementing particles in the positive electrode active layer.

[0147] 2. Free electrolyte composition test:

[0148] Discharge the battery with outer packaging with a current of 0.05C to 0% SOC (2.0V), cut a notch of about 0.5cm on the right side of the battery facing the positive column, and cut the same notch on the right side facing the negative column, ensuring that the two notches are on the diagonal line, and pour the free electrolyte into the fluoride bottle from the small opening on the side of the positive column until intermittent dripping flows down and count for 30s.

[0149] GC-MS and GC tests were used to collect the types and relative mass contents of formula I and other organic components in the electrolyte.

[0150] IC test was used to collect the relative mass content of additive A and salt types in the electrolyte.

[0151] 3. Non-free (pore) electrolyte test:

[0152] Remove the outer packaging, take out a single bare cell, quickly peel off the electrode, put it into an aluminum-plastic bag, add enough acetonitrile solvent to completely immerse the electrode, seal the aluminum-plastic bag containing acetonitrile solvent and electrode, and let it stand at 35±10℃ for 3 days.

[0153] GC-MS and GC tests were used to collect the types and relative mass contents of organic components in the electrolyte.

[0154] IC test was used to collect the relative mass content of additive A and salt types in the electrolyte.

[0155] 4. Free electrolyte R value test:

[0156] According to the test method disclosed in the reference "Reliable Values ​​of Electrochemical Stability Limits for Electrolytes", the LiFePO4 positive electrode (without lithium supplement particles) is assembled with a lithium sheet into a half-cell, charged to 5.4V at a constant current of 0.5C at 25°C, and left to stand for 30 minutes. The open circuit voltage of the overcharged battery is used as the initial point, and a cyclic voltammetry (CV) scan is performed at a scan rate of 5mV / s. The cutoff voltage is set to 3.8V, 4V, 4.2V, 4.4V, and 4.6V in each cycle. The reversible reaction charge QF and irreversible reaction charge QnF of each cycle in the CV process are obtained by integrating and summing the CV current, and the R value is obtained. The R value is plotted, and the R value at Umax is recorded as R e (or R z ).

[0157] 5. Cycle performance test

[0158] Charge to 3.65V at 0.5P constant power at 25℃, then discharge to 2.5V at 0.5P constant power. The energy of the Xth cycle of charge and discharge is recorded as CEx, DEx, until X=1000, and the capacity and energy values ​​of each cycle are recorded.

[0159] The battery energy efficiency is evaluated by the energy efficiency after cycling, η = DE 1000 / CE 1000 .

[0160] Experimental results:

[0161] Examples 1-18 and Comparative Examples 1-9 evaluated the effects of the design parameters of the free electrolyte and the non-free electrolyte on the cycle capacity retention rate at 45°C, 0.5P, and the energy efficiency after 1000 cycles. The results are shown in Table 1. Comparative Example 1 is a conventional one-time injection process, in which the electrolyte contains an ionic additive A, and a lithium supplement is introduced into the positive electrode. The cycle capacity retention rate and the energy efficiency after 1000 cycles of this technology are less than 90%, which has a lot of room for improvement. Comparative Example 2 uses a secondary injection process, but the electrolyte does not contain an ionic additive A, and a lithium supplement is introduced into the positive electrode. The cycle capacity retention rate and the energy efficiency after 1000 cycles of this technology are not as good as those of Comparative Example 1, indicating that without the introduction of the ionic additive A, the simple secondary injection process cannot significantly improve the cycle performance. Comparative Example 3 also uses a secondary injection process, but the ionic additive A is only introduced in the second injection, and the positive electrode introduces a lithium supplement. The application of this technology is slightly improved compared to Comparative Example 2, but the cycle capacity retention rate is not as good as that of Comparative Example 1, indicating that the ionic additive A is helpful to improve the cycle to a certain extent, which is consistent with the previously disclosed technology, but when the secondary injection process is combined, if the appropriate addition method is not adopted, the cycle capacity retention rate and energy efficiency cannot be improved at the same time, and the cycle capacity retention rate may not be as good as the primary injection process. Comparative Example 4 uses a secondary injection process and optimizes the addition method of the ionic additive A, but the positive electrode does not contain a lithium supplement. It can be seen that such an electrolyte adjustment improves the energy efficiency, but the cycle capacity retention rate is not as good as that of Comparative Example 1. By analyzing the comparative examples, it can be concluded that in order to improve the cycle capacity retention and energy efficiency, it is necessary to design the correlation between the secondary injection process, the ionic additive A in the electrolyte, and the positive electrode lithium supplement.

[0162] Based on the localized electrolyte design technology expected to be achieved by secondary injection, the m / R relationship between the oxidation stability of the free electrolyte and the ionic additive A in the non-free electrolyte is given. e , correlate the amount of ionic additive A in the non-free electrolyte and the demand for the designed amount of positive electrode lithium replenishment 1-m / M.

[0163] Examples 1-8 and Comparative Examples 5-7: By adjusting the type and designed amount M of the ionic additive A in an injection of electrolyte, R e , m and design parameter changes, Examples 9-12 and Comparative Example 8 adjust the proportion of lithium salt and other components in the second injection electrolyte to cause R e , m and design parameter changes, Examples 13-17 and Comparative Example 9 adjust the design addition amount of the positive electrode lithium supplement agent to cause R e , m and design parameter changes. By comparing the experimental results of the above embodiments and comparative examples, it can be learned that: ① By controlling the amount of additive A added in the first time, additive A can be enriched in the pores of the electrode, and its reduction product can be fully combined with the lithium supplement particles during the formation process, so that insufficient oxygen capture capacity will not occur due to insufficient addition, such as in comparative example 5; or excessive CEI impedance and cycle deterioration will not occur due to excessive addition, such as in comparative example 7. ② The R value (R z ) is low, the oxidation window of the free electrolyte is wide, R e is also low, which can avoid the accumulation of large amounts of by-products; if the R value (R z ) is too high, more by-products will be produced, which will affect the capacity retention rate and energy efficiency after the cycle. z Compared with the free electrolyte R e The slightly higher value is because there may be a reaction current generated by the additives that may be oxidized by the solvent in advance in the second injection. This part of the additives is slightly consumed during the injection and capacity test. ③ Add lithium supplement particles to the positive electrode active layer. During the first cycle of charging, the positive electrode lithium-rich electrode uses lithium supplement particles as a "sacrificial agent" to release lithium ions to replenish the irreversible lithium consumed by the negative electrode to form the SEI film, thereby increasing the energy density of the battery. However, when lithium supplement particles release lithium ions, they also release oxygen. Under high voltage, oxygen will accelerate the decomposition reaction of the components in the electrolyte, especially during high-temperature formation or high-temperature static aging, the reduction and oxidation decomposition of the electrolyte are more serious. As a result, a large amount of methane, ethylene, carbon dioxide and other gases overflow, and a large amount of alkyl lithium and lithium carbonate accumulate on the surface of the electrode, which in turn causes a decrease in energy efficiency and shortens the cycle life. The content w of lithium supplement particles in the positive electrode active layer has a suitable range of [0.3,3], which can achieve the advantage of cycle life without seriously deteriorating energy efficiency.

[0164] Example 18 comprehensively adjusted the electrolyte additive A in the first injection, the electrolyte composition in the second injection, and the content of the positive electrode lithium replenisher. When the localized electrolyte design parameters were met, the cycle capacity retention rate and the energy efficiency after 1000 cycles were further improved compared with Example 2, both exceeding 90%, which was significantly improved compared with the comparative example. It can be seen that the design requirements disclosed in this application are universal for the interactive effects of the injection process, electrolyte composition, and positive electrode lithium replenishment.

[0165] Examples 19-24

[0166] A battery was prepared according to the method described in Example 1, except that:

[0167] In Examples 19-23, the first and second injections of electrolyte are consistent with those in Example 2.

[0168] In Example 24, the first and second injections of electrolyte are consistent with those in Example 18.

[0169] The maximum voltage of the battery formation step is controlled according to the design value in Table 2, that is, the change of Umax is controlled. In the production process, except for the maximum voltage of the battery formation step, changes in other formation conditions that do not affect the realization of the claims and can achieve the expected technical effects are deemed to be within the scope of technical protection.

[0170] Table 2

[0171]

[0172] Examples 19-24 evaluated the effect of the maximum formation voltage on the characteristics, design parameters, and cycle of the localized electrolyte in the secondary injection process. In Example 19, the formation voltage is too low to fully activate the lithium supplement, so the performance is slightly different from that of Comparative Example 4, and is very different from the experimental results of Example 3 with the same positive electrode design and electrolyte design. In Example 23, the formation voltage is too high and the cycle performance is poor. This is because the excessively high formation voltage causes the positive electrode active material to over-delithiate, causing irreversible damage; the violent oxidative decomposition of the electrolyte will also consume a large amount of active lithium source and produce electrochemically unstable products, which are dispersed in the free electrolyte. The experimental results of Examples 20 to 22 show that with changes in the formation voltage, the degree of consumption of the ionic additive A and the oxidation stability of the electrolyte will also change accordingly, which is mainly manifested in the changes in the content of the ionic additive A in the non-free electrolyte and the Re of the free electrolyte, which mainly affects the design parameter m / R e , 1-m / M changes, when the design parameters exceed the protection range, it means that the ionic additive A in the non-free electrolyte cannot play its function of capturing oxygen free radicals / oxygen, and (or) the free electrolyte cannot maintain a fast ion channel. Example 24 finely adjusts the formation voltage based on Example 18, and can slightly improve the post-cycle energy efficiency without losing the cycle capacity retention rate, up to 96%.

[0173] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A battery, characterized in that: include: Positive electrode sheet, negative electrode sheet, separator and electrolyte; wherein, The positive electrode plate comprises a positive electrode active layer and a current collector, wherein the positive electrode active layer is arranged on the surface of the current collector, and the positive electrode active layer comprises lithium supplement particles; The separator is arranged between the positive electrode sheet and the negative electrode sheet; The electrolyte includes a non-free electrolyte and a free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet, and an electrolyte in the pores of the diaphragm; The non-free electrolyte includes an ionic additive, and the mass proportion m of the ionic additive in the non-free electrolyte is: 0.001%≤m≤2%; The R value R of the free electrolyte at the lithium potential e =0<R e <1.

2. The battery according to claim 1, characterized in that The battery meets the following conditions: 0<m / R e ≤2.5%; Wherein, m is the mass ratio of the ionic additive in the non-free electrolyte, R e is the R value of the free electrolyte at the potential relative to lithium.

3. The battery according to claim 1, characterized in that The mass proportion of the lithium supplement particles in the positive electrode active layer is 0.3%-3%.

4. The battery according to claim 2, characterized in that The ionic additive includes at least one of bis(oxalatoborate), difluoro(oxalatoborate), tri(oxalatophosphate), difluorobis(oxalatophosphate), and tetrafluoro(oxalatophosphate).

5. The battery according to claim 3, characterized in that The lithium supplement particle comprises a matrix and a coating layer, wherein the coating layer is arranged on the periphery of the matrix.

6. The battery according to claim 5, characterized in that The matrix is ​​Li5FeO4; And / or, the coating layer comprises oxide and carbon, wherein the chemical formula of the oxide is Z x O y , Z is selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, 1≤x≤3, 1≤y≤5; And / or, the coating layer has a thickness of 0.001 μm-1 μm.

7. A method for preparing the battery according to any one of claims 1 to 6, characterized in that: The steps of injecting electrolyte include: Performing a first liquid injection process using a first electrolyte; After the first liquid injection treatment, a chemical formation treatment is performed; After the chemical formation treatment, a second electrolyte injection treatment is performed. Wherein, the first electrolyte includes ionic additives.

8. The method according to claim 7, characterized in that The method meets the following conditions: 0.7≤(1-m) / M≤0.95, Wherein, m is the mass proportion of the ionic additive in the non-free electrolyte, and M is the mass proportion of the ionic additive in the first electrolyte; And / or, the R value R of the second electrolyte at the lithium potential z 0.1≤R z ≤3; And / or, the maximum charging voltage of the formation treatment is 3.9V-4.6V.

9. The method according to claim 8, characterized in that The mass ratio of the first electrolyte to the second electrolyte is (6:4)-(9:1); And / or, the sum of injection coefficients of the first electrolyte and the second electrolyte is 2.5g / Ah-5g / Ah.

10. An electrical device, characterized in that: A battery comprising any one of claims 1 to 6, or a battery prepared by the method of any one of claims 7 to 9.

Citation Information

Patent Citations

  • Negative electrode material for lithium ion battery, pre-lithiation treatment method of negative electrode material and lithium ion battery

    CN114975898A

  • Lithium ion battery based on cathode in-situ lithium supplement and preparation method thereof

    CN115663310A

  • Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    US20200083532A1

  • Secondary battery, battery module, battery pack and electric device

    WO2023184509A1